Day-to-day heart-rate variability recordings in World-Champion rowers: Appreciating unique athlete characteristics - Plews, D. J.; Laursen, P. B.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2017)
Purpose: Heart-rate variability (HRV) is a popular tool for monitoring autonomic nervous system status and training adaptation in athletes. It is believed that increases in HRV indicate effective training adaptation, but these are not always apparent in elite athletes.